UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI PENERAPAN METODE LATIHAN SISWA KELAS II SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Sri Heruwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by low yields social studies class II SD Negeri 010 BanjarPanjang Kecamatan Kerumutan. Of the 20 students hanya10 students (50.00%), whichreached the KKM. The purpose of this study is to improve learning outcomes IPS through theimplementation of training methods. This research is a class act, carried out by two cycles.Data of this research focuses on improving mastery learning and student learning outcomesIPS. Results of the study revealed that after the implementation of training methods hasllearning and increased student learning completeness. On the preliminary data the number ofstudents who completed is 10 students (50%) have increased in the first cycle by the numberof students 14 students (70%) and an increase in the second cycle by the number of students16 students (80%). Besides learning outcomes IPS sisaw also increased. In preliminary datathe average value of students is 55. In the first cycle increased to 60 and the second cycleincreased with an average value of 64.